Exploring the relationship between health literacy and fast food consumption: a population-based study from southern Iran - Namdar, Azam (BMC Public Health, 2021)
BACKGROUND: Health literacy (HL) may affect the consumption of fast food. We aimed to evaluate the effect of HL on fast food consumption among adult populations in Iran. METHODS: We evaluated HL and fast food consumption in 421 adult participants with age range of 18–65 years old in Fasa, Fars Province, southern Iran. Two-step cluster and systematic sampling was performed to recruit the study sample. Data were collected using a fast food consumption checklist, and the Health Literacy Instrument for Adults (HELIA) by face-to-face interviews. Population data across groups with and without fast food intake were compared. RESULTS: Most participants used fast food every few months (49.9%). People with low or unstable income consumed more fast food than others (P < 0.05). Sandwich and hotdog were the most consumed fast food (60.8%) followed by pizza (34.9%). Sausage and soda were the most seasoning food (66.7%). Most participants used fast food as dinner (67.9%) and with family (72.2%), suggesting the institutionalized consumption of this type of food in the family. Fun was the most frequent reason for the use of fast food (66.5%). Most participants completely knew about the raw materials for fast food and their adverse effects. Finally, we found that overall health literacy was lower among those who used fast food than those who did not. Consumed fast food (68.16 ± 23.85 vs. 73.15 ± 20.15; p = 0.021). This difference was also observed for some components of health literacy including reading skills, and decision-making subscales. CONCLUSIONS: The findings suggest there is a negative relationship between general health literacy and fast food consumption indicating that who possess lower level of health literacy is likely to consume more fast food. Specifically, the findings suggest that reading skills, and decision-making (behavioral intention) are more associated with decreased or increased fast food intake. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12889-021-10763-3.